Inoculation With Growth-Promoting Bacteria Associated With the Reduction of Phosphate Fertilization in Sugarcane - Rosa, Poliana Aparecida Leonel; Mortinho, Emariane Satin; Jalal, Arshad; Galindo, Fernando Shintate; Buzetti, Salatiér; Fernandes, Guilherme Carlos; Barco Neto, Maurício; Pavinato, Paulo Sergio; Teixeira Filho, Marcelo Carvalho Minhoto (Frontiers in Environmental Science, 2020)
Sugarcane holds the prominent position in global economy. Extensive research is needed to enhance the efficiency of phosphorous fertilizers which increase the cost of sugarcane production more specifically in the less fertile soils which are weathered and phosphorous deficit as tropical region soils. We are currently living in a transitional period called the "Green Micro-revolution", in which the use of plant growth-promoting bacteria (PGPB) is justified and although bacteria such as A. brasilense, Bacillus and P. fluorescens in other crops are recognized for increasing production however, little is known about the effects of these microorganisms on sugarcane. The current study aimed to evaluate the effect of inoculation with three species of plant growth promoting bacteria (Azospirillum brasilense, Bacillus subtilis and Pseudomonas fluorescens) without or with combine application of reduced doses of phosphate fertilizer, in the P soil available, P leaf concentration, shoot yield and P accumulation in sugarcane (cane-plant) at the end of the cycle. The experiment was carried out with a sugarcane crop in a Hapludox Rhodic with low available P content, in a randomized block design with 8 x 5 factorial scheme, being eight inoculations and five P doses (0, 45, 90, 135 and 180 kg ha-1 P2O5) as triple superphosphate. The bacterial inoculations influenced the leaf P content, so that inoculation with B. subtilis + P. fluorescens provided the highest concentration of phosphorus in the sugarcane leaf. Both the layers of the soil were differently influenced by inoculation and P doses whereas inoculation with A. brasilense + P. fluorescens at 135 kg P2O5 ha-1 provided the highest soil P content in the soil layer of 0-0.25 m. Although, maximum stalk yield was obtained with inoculation of B. subtilis + P. fluorescens at the dose of 135 kg ha-1 P2O5. The inoculation of A. brasilense + B. subtilis with application of 45 kg P2O5 ha-1 improved dry matter, total P accumulation and stalk production by 38% in sugarcane variety (RB92579) and reduced P fertilization by 75% for the same variety grown in low-P soil.